The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14710/jitaa.44.1.65-76
|View full text |Cite
|
Sign up to set email alerts
|

Modelling hatchability and mortality in muscovy ducks using automatic linear modelling and artificial neural network

Abstract: This study was embarked upon to predict hatchability and mortality rate of Muscovy ducks in Nasarawa State, Nigeria. Data were obtained from a total of 119 duck farmers. The automatic linear modelling (ALM) and artificial neural network (ANN) models were employed. The average flock size was 9.84±0.60 per household. The predicted hatchability mean values using ALM (8.66) and ANN (8.65) were similar to the observed value (8.66). The predicted mortality mean values using ALM (2.95) and ANN (3.03) were also simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Kuningan and Majalengka Muscovy's high adaptability to the research location's temperature (Jatinangor) may contribute to this low rate. This result confirmed that a contributing factor to livestock mortality is their adaptability to the environmental condition [11]. This study's average mortality rate of drake and duck Muscovy ducks was better than 8.33% [7] on Muscovy ducks aged 0-6 months.…”
Section: ) Feed Consumptionsupporting
confidence: 77%
See 2 more Smart Citations
“…Kuningan and Majalengka Muscovy's high adaptability to the research location's temperature (Jatinangor) may contribute to this low rate. This result confirmed that a contributing factor to livestock mortality is their adaptability to the environmental condition [11]. This study's average mortality rate of drake and duck Muscovy ducks was better than 8.33% [7] on Muscovy ducks aged 0-6 months.…”
Section: ) Feed Consumptionsupporting
confidence: 77%
“…The gizzards of drake mallard and Muscovy ducks reared under the semi-intensive maintenance tend to be heavier than those in the intensive maintenance. This situation could be due to the increased intake of high-fiber feed in the semi-intensive maintenance, whereas intensive farming has provided all important nutrition for Muscovy ducks in their feed [3], [11].…”
Section: K1 K2 K3 K4mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we ran the ALM analysis to find the most stable (reliable) model for the ANN analysis. The ALM was introduced in IBM SPSS Version 19 and enabled researchers to automatically select the best subset (Oshima and Dell-Ross 2016 ), i.e., the ALM assists us in choosing the best model for subsequent ANN (or regression) analyses (Yakubu et al 2019 ). ALM has several computational and technical advantages over traditional linear regression approaches.…”
Section: Introductionmentioning
confidence: 99%